The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/imhj.10085
|View full text |Cite
|
Sign up to set email alerts
|

Predicting maternal reactivity/sensitivity: The role of infant emotionality, maternal depressiveness/anxiety, and social support

Abstract: It was hypothesized that an accumulation of unfavorable conditions, i.e., high negative emotionality and low positive emotionality of the infant, maternal depression and anxiety, and lacking social and emotional support can attenuate mothers' reactivity/sensitivity. Maternal reactivity/sensitivity was observed during home visits and in the laboratory. Infant negative and positive emotionality was assessed by mother reports and behavioral observations. Maternal depressiveness/anxiety as well as social support w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(57 citation statements)
references
References 41 publications
4
46
0
6
Order By: Relevance
“…A significant proportion of this variation within the sample (23%) could be explained by variations in educational level and social support. This confirms findings in previous studies (Mertesacker, Bade, Haverkock, & Pauli-Pott, 2004;Mesman, Van IJzendoorn , & Bakermans-Kranenburg, 2012) and suggests that the sensitivity observations tapped into meaningful variations in parenting patterns in this sample. This is further corroborated by the nonsignificant correlations between sensitivity and camera-related behaviors, showing that camera shyness did not unduly affect sensitivity scores.…”
Section: Discussionsupporting
confidence: 89%
“…A significant proportion of this variation within the sample (23%) could be explained by variations in educational level and social support. This confirms findings in previous studies (Mertesacker, Bade, Haverkock, & Pauli-Pott, 2004;Mesman, Van IJzendoorn , & Bakermans-Kranenburg, 2012) and suggests that the sensitivity observations tapped into meaningful variations in parenting patterns in this sample. This is further corroborated by the nonsignificant correlations between sensitivity and camera-related behaviors, showing that camera shyness did not unduly affect sensitivity scores.…”
Section: Discussionsupporting
confidence: 89%
“…In two such studies, high scores on a separation anxiety questionnaire were associated with overprotective maternal behavior (Hock, McBride, & Gnezda, 1989;Stifter, Coulehan, & Fish, 1993); in one, mothers' retrospective accounts of felt anxiety after a premature birth were related to intrusive maternal behavior at 6 months' postpartum (Wijnorks, 1999); and in several studies, prenatal anxiety was related to intrusive and controlling behavior during the early postpartum period (Field, Sandberg, Vega-Lahr, Goldstein, & Guy, 1985;Heinicke, Diskin, Ramsey-Klee, & Given, 1983). Added to this list is the study of Feldman, Greenbaum, Mayes, and Erlich (1997), which showed that an increase in mothers' trait anxiety scores from 3 to 9 months' postpartum was associated with a concurrent decrease in maternal sensitivity (but not intrusiveness) (also see Mertesacker, Bade, Haverkock, & Pauli-Pott, 2004).…”
Section: Anxious-overactive Mothersmentioning
confidence: 94%
“…The mother helps protect the infant's airway during feeding and provides comfort by aiding the infant in maintaining regulated behavioral, emotional, and physiological processes. Research has shown that maternal sensitivity to infant signals and timely and appropriate responsiveness to the infant's signals, pacing, and preferences are associated with positive infant developmental outcomes (Ainsworth, 1983;Egeland & Farber, 1984;Isabella, 1993;Mertesacker, Bade, Haverkock, & Pauli-Pott, 2004). Maternal sensitive and responsive behaviors during feeding are important for infant feeding outcomes (DeWitt et al, 1997;Pridham, Brown, Clark, Sondel, & Green, 2002;Thoyre & Brown, 2004;Valenzuela, 1997).…”
Section: Regulatory Aspects Of Mother-infant Interactionmentioning
confidence: 99%